Revitalisasi Masjid Sebagai Pusat Pembelajaran Keagamaan Dan Sosial - Saifuddin; Muhammad Nusur; Muh, Irwan T; Marsyud; Rahmah Muin (CV. BAROKAH PUBLISHER, 2026)
The Unasman Multimatik Village Development Program (PUMD) class 41 of Al-Asyariah Mandar University in 2026 was carried out in groups by each student to create products that can be utilized or can educate the target community. Landi Kanusuang Village, Mapilli District, Polewali Mandar Regency is one of the locations for this Unasman Multimatik Village Development Program (PUMD). Based on the village problems that have been previously revealed, a seminar for mosque administrators and mosque youth is very much needed. In designing this activity, first determine the concept in this case integrating the work program to be implemented. In the implementation of this program is aimed at the community, especially mosque administrators and mosque youth. Counseling and socialization media can improve the understanding of mosque administrators and mosque youth regarding the work program that we are implementing. Socialization or counseling regarding Mosque Revitalization as a center for religious and social learning is expected to provide an understanding of the 4 pillars of the main function of the mosque to mosque administrators and mosque youth in Landi Kanusuang village. The mosque revitalization outreach program, which serves as a center for religious and social learning, is also expected to educate the community, particularly mosque administrators and youth, about the four main pillars of the mosque's function: as a center for worship and spirituality, a center for education, a center for social empowerment, and a center for recovery or guidance.